2017
DOI: 10.1101/cshperspect.a028613
|View full text |Cite
|
Sign up to set email alerts
|

Development, Diversity, and Function of Dendritic Cells in Mouse and Human

Abstract: The study of murine dendritic cell (DC) development has been integral to the identification of specialized DC subsets that have unique requirements for their form and function. Advances in the field have also provided a framework for the identification of human DC counterparts, which appear to have conserved mechanisms of development and function. Multiple transcription factors are expressed in unique combinations that direct the development of classical DCs (cDCs), which include two major subsets known as cDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 163 publications
(219 reference statements)
4
65
0
Order By: Relevance
“…Recent whole-transcriptome analyses of DCs during homeostatic and inflammatory maturation found suppression of Mycl, suggesting that its expression is most likely limited to immature cDCs (25,26). Thus, we examined Mycl-GFP expression in Mycl gfp/+ mice, using CCR7 expression as a canonical marker of maturation status of DCs in peripheral lymphoid organs (28 confirming that Mycl expression is suppressed on maturation in this tissue ( Fig. 1 A and B).…”
Section: Mycl Is Highly Expressed In Cdc1s and Is Repressed On Homeossupporting
confidence: 62%
See 1 more Smart Citation
“…Recent whole-transcriptome analyses of DCs during homeostatic and inflammatory maturation found suppression of Mycl, suggesting that its expression is most likely limited to immature cDCs (25,26). Thus, we examined Mycl-GFP expression in Mycl gfp/+ mice, using CCR7 expression as a canonical marker of maturation status of DCs in peripheral lymphoid organs (28 confirming that Mycl expression is suppressed on maturation in this tissue ( Fig. 1 A and B).…”
Section: Mycl Is Highly Expressed In Cdc1s and Is Repressed On Homeossupporting
confidence: 62%
“…It is widely accepted that DC maturation correlates with the capacity of DCs to effectively regulate immune responses (28). The present study reveals mechanisms by which MYCL and MXD1 regulate cellular fitness in a primary cell lineage.…”
Section: Discussionmentioning
confidence: 63%
“…The GCN analysis did identify three separate DC-associated co-expression clusters that are consistent with current knowledge of putative DC subsets and adaptation in mice [20,21,106]. Cluster 13 includes Ccr7 and transcription factors Spib and Stat4, Cluster 28 includes Flt3, Kit and the transcription factor Relb and Cluster 49 includes cDC1 markers Itgae (CD103) and Xcr1.…”
Section: Dendritic Cell Co-expression Clusterssupporting
confidence: 76%
“…Immunofluorescence and paracellular permeation studies of normal human trunk skin, mouse ear, abdominal skin and back skin revealed that only a single layer of cells, the SG2 cell layer, is equipped with TJs that limits paracellular molecular movement and divides cell membrane into apical and basolateral membrane. [4,7,25,35] In the immunofluorescent studies using vertical sections of the skin, TJ-forming cell should be determined by the combination of three characteristics shown below. [7] One is the localization of ZO-1 or occludin at the apical edge of the lateral cell-cell contact.…”
Section: The Role Of Tjs In the S K In Barrier Sys Temmentioning
confidence: 99%